Hydrogen sulfide mediates the vasoactivity of garlic - Benavides, Gloria A; Squadrito, Giuseppe L; Mills, Robert W; Patel, Hetal D; Isbell, T. Scott; Patel, Rakesh P; Darley-Usmar, Victor M; Doeller, Jeannette E; Kraus, David W (Proceedings of the National Academy of Sciences - PNAS, 2007)
The consumption of garlic is inversely correlated with the progression of cardiovascular disease, although the responsible mechanisms remain unclear. Here we show that human RBCs convert garlic-derived organic polysulfides into hydrogen sulfide (H₂S), an endogenous cardioprotective vascular cell signaling molecule. This H₂S production, measured in real time by a novel polarographic H₂S sensor, is supported by glucose-maintained cytosolic glutathione levels and is to a large extent reliant on reduced thiols in or on the RBC membrane. H₂S production from organic polysulfides is facilitated by allyl substituents and by increasing numbers of tethering sulfur atoms. Allyl-substituted polysulfides undergo nucleophilic substitution at the α carbon of the allyl substituent, thereby forming a hydropolysulfide (RSnH), a key intermediate during the formation of H₂S. Organic polysulfides (R-Sn-R'; n > 2) also undergo nucleophilic substitution at a sulfur atom, yielding RSnH and H₂S. Intact aorta rings, under physiologically relevant oxygen levels, also metabolize garlic-derived organic polysulfides to liberate H₂S. The vasoactivity of garlic compounds is synchronous with H₂S production, and their potency to mediate relaxation increases with H₂S yield, strongly supporting our hypothesis that H₂S mediates the vasoactivity of garlic. Our results also suggest that the capacity to produce H₂S can be used to standardize garlic dietary supplements.